Geographic Expansion of Japanese Encephalitis Virus to Australia: Neuroinflammatory Sequelae and Consideration of Immunomodulation. Issue 5 (16th February 2023) - Cole, Elizabeth; Boast, Alison; Yiu, Eppie M.; Kornberg, Andrew J.; Jadhav, Trupti; Mignone, Cristina; Abo, Yara-Natalie; Britton, Philip N.; Osowicki, Joshua; Macdonald-Laurs, Emma
Abstract : We report a child from Southern Australia (New South Wales) who presented during a La Niña event with encephalopathy and acute flaccid paralysis. Magnetic resonance imaging suggested Japanese encephalitis (JE). Steroids and intravenous immunoglobulin did not improve symptoms. Therapeutic plasma exchange (TPE) resulted in rapid improvement and tracheostomy decannulation. Our case illustrates the complex pathophysiology of JE, its' geographic expansion into Southern Australia and potential use of TPE for neuroinflammatory sequelae.